Making accounting education fit for purpose for the new economy - HO, Yew Kee (Institutional Knowledge at Singapore Management University, 2024)
The accountancy profession faces one of its most challenging periods as several factors converge to disrupt it. Technological advancements, the expanding role of accountants, declining student interest in accountancy, and increasing expectations for uniquely human capital all exert pressure on the profession to reinvent itself or face marginalisation. This study, funded by the Institute of Singapore Chartered Accountants (ISCA), examines trends in the accountancy profession alongside accountancy education in Singapore. Its goal is to formulate a fit-for-purpose accountancy education for the new economy.